3,4-methylenedioxymethamphetamine (MDMA) impairs the extinction and reconsolidation of fear memory in rats - Hake, Holly S. (Physiol Behav, 2018)
Clinical trials have demonstrated that 3,4-methylenedioxymethamphetamine (MDMA) paired with psychotherapy is more effective at reducing symptoms of post-traumatic stress disorder (PTSD) than psychotherapy or pharmacotherapy, alone or in combination. The processes through which MDMA acts to enhance psychotherapy are not well understood. Given that fear memories contribute to PTSD symptomology, MDMA could augment psychotherapy by targeting fear memories. The current studies investigated the effects of a single administration of MDMA on extinction and reconsolidation of cued and contextual fear memory in adult, male Long-Evans rats. Rats were exposed to contextual or auditory fear conditioning followed by systemic administration of saline or varying doses of MDMA (between 1 and 10 mg/kg) either 30 min before fear extinction training or immediately after brief fear memory retrieval (i.e. during the reconsolidation phase). MDMA administered prior to fear extinction training failed to enhance fear extinction memory, and in fact impaired drug-free cued fear extinction recall without impacting later fear relapse. MDMA administered during the reconsolidation phase, but not outside of the reconsolidation phase, produced a delayed and persistent reduction in conditioned fear. These findings are consistent with a general memory-disrupting effect of MDMA and suggest that MDMA could augment psychotherapy by modifying fear memories during reconsolidation without necessarily enhancing their extinction.